The housing problem in Italy - ALBERTI, S. (PSL Quarterly Review, 2014)
The article considers the other most pressing of Italian problems, i.e. the scarcity of dwellings which in Italy has much more serious features than in other Western European countries, including those that have suffered most seriously from war destructions. The author examines first the special features of the housing question in Italy since 1931, given data for the number of dwellings, new buildings, war destructions, sanitary conditions, over-crowding, internal migrations, etc., and goes on to describe some of the consequences of the legal restrictions placed on rents, as shown by the new economic and social relations between landlords and tenants, the supply of dwellings, and, above all, by the more rapid deterioration of house property, one of the more serious factors making for the destruction of national wealth. Finally, he deals with the measures taken by the government to encourage building. JEL: O18, R12, R31